A protocol for making and sectioning multiple embedded Swiss-rolls in a gelatin matrix - Sohrabi, Mona (MethodsX, 2019)
The appropriate methodological approach for intestinal preparation enables researchers to create representative histological and immunostaining images which validate their biochemical data. The Swiss-roll technique was first introduced by Reilly and Kirsner in 1965. Later, Moolenbeek and Ruitenberg described a detailed procedure to longitudinally study the rodent intestine in 1981 [1]. In this publication, our slightly different approach for co-embedding four different Swiss-rolls in a gelatin block provides a full-length overview of cross-sectional colons on a single slide. This protocol allows for longitudinal histologic examination of multiple tissue samples on a single slide simultaneously. In this method, antigenicity is retained for immunohistology. In addition, the accessibility of samples during the prolonged hardening time required of the gelatin matrix allows the tissue samples to be adjusted/re-adjusted to provide the desired orientation and spatial arrangement for ideal cross sections with similar planes of section and optimum space utilization for slide mounting. Although not the focus of this protocol, the room temperature stability of the gelatin matrix and the ability to contain numerous tissue samples in a block allows the flexibility of performing thicker sections for free-floating tissue staining and ease of mounting a single gelatin sheet rather than individual tissue sections. This is a convenient approach for allowing precise preparation of multi-tissue blocks and simultaneous sectioning, staining, and slide mounting of tissue for subsequent comparisons. • A single gelatin block is prepared by simultaneously embedding at least four different intestinal Swiss-rolls. • The tissue orientation can be adjusted for each sample as desired which facilitates the comparison of different colon samples on a single gelatin section. • The gelatin sections containing tissue samples are stable at least overnight at room temperature for staining.